2018
DOI: 10.1016/j.bmcl.2018.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of longanlactone analogues as neurotrophic agents

Abstract: Longanlactone analogues were synthesized using a route featuring Friedel-Crafts acylation, Sonogashira coupling and 1,3-dipolar cycloaddition reactions. Structure-activity relationships were investigated for neurotrophic activity. Compound 6 was found to have the most potent neurotrophic activity among all the synthesized analogues in Neuro2a cells as evidenced by a battery of in vitro/cell based assays for assessment of neurogenic and potential neurotrophic activity including neurite outgrowth assay and real … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…134 1,2,3-Triazoles bearing longanlactone analogues were synthesised for potential enhanced neurotrophic activity. 135 The in vitro cell cytotoxic potentials of the synthesised natural product derivatives were examined against mouse neuroblastoma cells (Neuro-2a). Among the 1,2,3-triazole-containing derivatives, 105 (Fig.…”
Section: 23-triazoles As Neuroprotective Agentsmentioning
confidence: 99%
“…134 1,2,3-Triazoles bearing longanlactone analogues were synthesised for potential enhanced neurotrophic activity. 135 The in vitro cell cytotoxic potentials of the synthesised natural product derivatives were examined against mouse neuroblastoma cells (Neuro-2a). Among the 1,2,3-triazole-containing derivatives, 105 (Fig.…”
Section: 23-triazoles As Neuroprotective Agentsmentioning
confidence: 99%
“…The data analysis revealed that both G1 and G2 at three different concentrations show significant neurotrophic activity when compared with the N2A cells in the absence of the compounds (* p < 0.05) (Figure ). It was found that neurotrophic factors such as BDNF (brain derived neurotrophic factor), glial derived neurotrophic factor (GDNF), neurotropin 3 (NT3), NGF, and vascular endothelial growth factor (VEGF) significantly increased in the presence of most of the concentrations of both G1 and G2 …”
Section: Results and Discussionmentioning
confidence: 99%
“…43 Sulforhodamine B (SRB) Assay. The cytotoxicity against N2A using two different GQDs was assessed (G1, G2) with five different concentrations (10,25,50,75, and 100 μg mL −1 ) using SRB assay after 24 h of incubation. N2A cells were passaged and plated in a 96well plate at a seeding density of 9600 cm 2 per well.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The physicochemical factors including the H-bond donor, H-bond acceptor, molecular weight, cLog P , and topological polar surface area of the compounds were used to generate the BBB score (log BB) using a boiled egg model 21 and the Swiss ADME protocol. 22 The BBB crossing ability of all 15 compounds was calculated using the in silico online blood–brain barrier prediction server [] as reported earlier 23 and most of the compounds were found to be BBB permeable except compounds 8f , 8i , 8j and 9a .…”
Section: Biological Evaluationmentioning
confidence: 99%